2019
DOI: 10.1007/s13320-019-0576-3
|View full text |Cite
|
Sign up to set email alerts
|

Design of a Plasmonic Platform to Improve the SERS Sensitivity for Molecular Detection

Abstract: We suggested a plasmonic platform based on a cubic pattern of gold spheres for surface enhanced Raman spectroscopy (SERS). In the case of linear polarization along the symmetry axes, the SERS enhancement per area is identical to hexagonally patterned surfaces. The validity of this model was tested using the simulation package of COMSOL Multiphysics® Modeling Software. We found an improved sensitivity in the near infrared and visible region of the electromagnetic spectrum. This method considered tolerance towar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(4 citation statements)
references
References 40 publications
0
4
0
Order By: Relevance
“…Surface-enhanced Raman spectroscopy (SERS) depends on plasmonic platforms and nano-antenna, which have developed into an effective area of study [ 83 ]. SERS is one of the leading techniques for label-free ultrasensitive vibrational fingerprinting of a variety of compounds.…”
Section: Monitoring Biological and Chemical Threats Agentsmentioning
confidence: 99%
See 1 more Smart Citation
“…Surface-enhanced Raman spectroscopy (SERS) depends on plasmonic platforms and nano-antenna, which have developed into an effective area of study [ 83 ]. SERS is one of the leading techniques for label-free ultrasensitive vibrational fingerprinting of a variety of compounds.…”
Section: Monitoring Biological and Chemical Threats Agentsmentioning
confidence: 99%
“…They also performed the crossselectivity experiments with Zika-virus-infected patients and showed that this sensor can distinguish Dengue virus serotype infected individual patients. Surface-enhanced Raman spectroscopy (SERS) depends on plasmonic platforms and nano-antenna, which have developed into an effective area of study [83]. SERS is one of the leading techniques for label-free ultrasensitive vibrational fingerprinting of a variety of compounds.…”
Section: Biological Threats Agentsmentioning
confidence: 99%
“…Although the exact mechanism of SERS is still under discussion, it is widely accepted that the surface enhancement effect arises from two processes: electromagnetic and chemical enhancement [5,6]. In the case of electromagnetic enhancement (EM), the SERS effect occurs from the interaction between the incident laser photons and the surface plasmons, which are the collective oscillating frequencies of the conducting electrons found on the surface of the metallic nanostructure [7,8]. The efficiency of this method relies on the distance between the analyte and the metal nanoparticle (NP); thus, only molecules which are near the NP, referred to as the "hotspot", will experience the maximum Raman signal amplification [9,10].…”
Section: Introductionmentioning
confidence: 99%
“…Metal-based nanomaterials are a key element in the development of advanced nanotechnology. These nanomaterials are promising candidates for a variety of applications including optical sensors and biosensors technology [1][2][3][4], photochemistry and photocatalysis [5][6][7][8]. Particularly, metallic nanoparticles NPs attracted substantial interest due to their Localized Surface Plasmon Resonance (LSPR).…”
Section: Introductionmentioning
confidence: 99%